AN OVERVIEW ON ROLE OF HUMAN RESOURCE MANAGEMENT (HRM) ON BUSINESS DEVELOPMENT– A CASE STUDY OF AUTO INDUSTRY - M. , SAKTHIVEL MURUGAN; T., SUJATHA (International Journal of Psychosocial Rehabilitation, 2020)
Strategic human resource management practices create good relationships between organizations and employees. Further, it is a tool to develop the commitment of employees for the betterment of the business. Organizational commitment of employees provides a base and willingness to contribute more efforts to the organization and also to achieve its goals and objectives. This paper is aimed at studying how strategic human resource management as a tool to achieve organizational commitment and business development auto industry.